2007
DOI: 10.1016/j.clinph.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

An open study of repetitive transcranial magnetic stimulation in treatment-resistant depression with Parkinson’s disease

Abstract: TMS may be beneficial for depressed PD patients in multiple functional domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 38 publications
3
47
1
4
Order By: Relevance
“…In MDD associated with Parkinson's disease, several open and controlled studies have been published, showing consistent improvement of depressive symptoms as well as motor symptoms after prefrontal stimulation [132][133][134][135][136] . Two randomized controlled trials showed that the efficacy of rTMS is similar to fluoxetine in patients with this condition, but with less adverse events 133,135 .…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In MDD associated with Parkinson's disease, several open and controlled studies have been published, showing consistent improvement of depressive symptoms as well as motor symptoms after prefrontal stimulation [132][133][134][135][136] . Two randomized controlled trials showed that the efficacy of rTMS is similar to fluoxetine in patients with this condition, but with less adverse events 133,135 .…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…A recent study showed that ten to 15 sessions of rTMS applied on the left DLPFC at a frequency of 10Hz, and an intensity of 110% MT was associated with significant reduction of depressive symptoms by 30% and a remission rate of 10% as compared to placebo intervention. Mild and few adverse effects such as headache were reported [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] . Another advantage of the use of rTMS is the improvement in executive functions by rTMS 150,151 .…”
Section: Mdd In the Rehabilitation Settingmentioning
confidence: 99%
“…[71][72][73][74][75][76][77][78][79] A recent meta-analysis of RCTs for the use of rTMS for the treatment of depressive symptoms in PD found rTMS to be superior to sham treatment in reducing depressive symptoms in PD, and to have similar efficacy as SSRIs, with the possible benefit of simultaneous improvement in motor symptoms. 80 Another meta-analysis found the effect of rTMS on depression in PD to be nonsignificant, based on the two existing RCTs.…”
Section: Alternative Treatmentsmentioning
confidence: 99%
“…rTMS treatment in PD generally aims at improving motor symptoms, such as LIDs, bradykinesias and freezing of gait (FOG), though some studies also focused on non-motor symptoms, including depression and apathy [21], speech and voice [22,23] and cognitive functions [24].…”
Section: Rtms Rationale In Parkinson's Diseasementioning
confidence: 99%